Conditions during expander processing of soybean meal and raw soybeans affect nutrient digestibility in finishing pigs - S L Traylor; Robert H Hines; N Amornthewaphat; S L Johnson; P Sorrell; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1998)
Expander processing improved nutrient digestibility in diets with soybean meal and raw soybeans. Furthermore, with 600 psi cone pressure (20 k Wh/tonon ofspecific energy input), the diets with raw soybeans had equal or greater digestibility of nutrients compared to the soybean meal-based control diet.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Expander; Soybean; Digestibility; Finishing pigs